Compensation practices in the Nigerian public service : analysis of wage differential / Aliyu O Ashiru - Ashiru, Aliyu O (Universiti Teknologi MARA, Shah Alam, 2019)
In spite of global conventions, declarations, and other legal framework established to promote equity in compensation for work of equal value and to abolish discriminatory reward system in both public and private sector organizations, discriminatory compensation has remained unabated in Nigerian public service. Although, several attempt has been made to redress these anomalies but proved abortive. This study acknowledges the various theoretical arguments to justify pay disparity. The main thrust of this paper centers on examining the pattern of inter-sectorial wage structure. The study adopted secondary source of data where figures of salary structure were extracted from the quarterly report of National Salaries, Income, and Wages Commission; data collated were analyzed using coefficient of variation. This paper found a huge pay gap (i.e., highly discriminatory) wage structure which could obviously transcend to industrial disharmony, hence affect public service stability and effective performance. The study holds firm convictions that pay parity amongst categories of workers in workplace is sin qua non to harmonious working environment (quid pro quo). Therefore, the study recommends that pay equity remains a fundamental human right, most especially for worker whose job description, objective, and criteria for recruitment are similar, this is capable of bridging the inequality gap, promote mentorship, and stability, hence strengthened institutional capacity for better service delivery.